Amphiphilic fluorescent probe self-encored in plasma to detect pH fluctuations in cancer cell membranes. Issue 5 (21st December 2020) - Podder, Arup; Joseph, Manu M.; Biswas, Shayeri; Samanta, Sanjib; Maiti, Kaustabh K.; Bhuniya, Sankarprasad
Abstract : Newly developed an amphiphilic "turn-on" fluorescent probe (P1 CS ) enables to distinguish of cancer cells from normal cells through mapping of pH fluctuations in cell-surface. Abstract : We have developed an amphiphilic pH probe (P1 CS ) to detect pH levels in the plasma membrane in cancer cells. An elevated fluorescence signal at 550 nm at the cell surface of cancer cells (MDA-MB-231, HeLa cells) prompted the application of P1 CS as a pH marker for the cancer cell surface, discriminating it from normal cells (WI-38). Moreover, the probe enables labeling of the surface of multilayered tumor spheroids, which promotes its use as a marker for the surface of tumor tissue.